Scholars and priests - Franck, Irene M. 4 0 16; Brownstone, David M.; 5 (New York : Facts on File, 1988)
Traces the historical development of the occupations of teachers, priests, scholars, and educators.
Includes index.
Bibliography: p. 187-191.
8.9;Young Adult;Young Adult
Keywords: 2 -- 0; 6; History;History;History;History;History;History.;History.;History.;History. -- Teachers;Priests;Scholars;Educators;Occupations;Teachers;Priests;Scholars;Educators -- Juvenile literature.;Juvenile literature.;Juvenile literature.;Juvenile literature.;Juvenile literature; 20; 2